SMART TECHNOLOGIES IN TEACHING "INFORMATION TECHNOLOGIES IN CONSTRUCTION" EFFICIENCY OF THE USE MODEL - M.M.Usanov; Z.M.O‘rinboyev (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
It is written about the effectiveness of the model of using SMART technologies in teaching the subject "Information technologies in construction" to improve the knowledge, skills and abilities of students.